2020
DOI: 10.1007/s10551-020-04614-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spirituality and Religiosity on the Ethical Judgment in Organizations

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 177 publications
(298 reference statements)
1
19
0
2
Order By: Relevance
“…Reductively assuming that because an individual is "spiritual", she would disengage from "unethical" actions is misguided. This may shine a light on studies that have found a relationship between religion/spirituality and unethical behavior (Alshehri et al 2020;Zhang, 2020). Our study shows how a deeper understanding of the normative content of different traditions would greatly enhance this stream of scholarship.…”
Section: Practical Implicationsmentioning
confidence: 70%
“…Reductively assuming that because an individual is "spiritual", she would disengage from "unethical" actions is misguided. This may shine a light on studies that have found a relationship between religion/spirituality and unethical behavior (Alshehri et al 2020;Zhang, 2020). Our study shows how a deeper understanding of the normative content of different traditions would greatly enhance this stream of scholarship.…”
Section: Practical Implicationsmentioning
confidence: 70%
“…Reductively assuming that because an individual is "spiritual", she would disengage from "unethical" actions is misguided. Further research may shine a light on studies that have found a relationship between religion/spirituality and unethical behaviour (Alshehri et al, 2020;Zhang, 2020). Our study shows how a deeper understanding of the normative content of the interplay between meaningful work and different traditions would greatly enhance this stream of scholarship.…”
Section: Conclusion and Avenues For Future Studiesmentioning
confidence: 70%
“…Yönetim literatüründe, ahlak, maneviyat, dindarlık ve etik yargı arasında bağlantı olduğuna dair çalışmalar da söz konusu olmaya başlamıştır. Kişilerin dini, ahlaki ve manevi görüşlerinin, örgütlerdeki etik yargılarını etkilediği ve bu sürece onların dini uygulamaları ve bilgileriyle (davranışsal ve entelektüel bileşenler) aracılık ettiğine yönelik bulgular vardır (Alshehri, 2020). Bu bulguyu destekler nitelikte Giacalone ve Jurkiewicz (2003), bireysel maneviyat ve etik davranış arasında bir ilişki olduğunu tespit etmiştir.…”
Section: Ahlak Ve Etik Kavramıunclassified